Solid Electrolyte Membrane Reactor for Ammonia Synthesis - กลิ่นศรีสุข, สุจิตรา (KKU Science Journal, 2014)
Ammonia has been industrially synthesized from its elements, H2 and N2, via HaberBosch process for almost 100 years. This conventional process performs under high pressure and requires specific catalysts. The highest conversion of Haber-Bosch process is only 10-20% due to thermodynamic limitation. Also, large amount of CO2 is emitted from the use of natural gas as hydrogen source. To resolve the problems, alternative processes have been proposed. Electrochemical process is one of the most promising processes. In electrochemical cells, ammonia is synthesized under atmospheric pressure and without thermodynamic limitation. Comparing with other types of electrolytes, solid electrolytes offer cells with scalable and robust components. Among those solid electrolytes, proton conducting oxide and polymer electrolytes provide the highest rate of ammonia formation. In addition, proton conducting electrolytes have revealed the possibility of ammonia production from water instead of gaseous hydrogen. Therefore, CO2 emission and the overall costs would be significantly reduced. Electrocatalysts are also the important component especially the catalyst for the ammonia formation reaction. It is likely that the sluggish-dissociation reaction of nitrogen molecule on the catalyst surface could be the rate determining step for the formation reaction. In this review, other factors that affect the reactor efficiency including optimized conditions and component requirements are also discussed.